Respuesta :

Answer:

[tex]m=-7[/tex]

Step-by-step explanation:

[tex]6m-6=9m+15[/tex]

Add 6 to both sides:

[tex]6m-6+6=9m+15+6[/tex]

[tex]6m=9m+21[/tex]

Subtract 9m from both sides:

[tex]6m-9m=9m+21-9m[/tex]

[tex]-3m=21[/tex]

Divide both sides by -3:

[tex]\frac{-3m}{-3}=\frac{21}{-3}[/tex]

[tex]m=-7[/tex]

Answer:

m = -7

Step-by-step explanation:

  1. Combine like factors. It should now look like this: 6m - 9m = 6 + 15
  2. 6 + 15 = 21
  3. Plug 21 in: 6m - 9m = 21
  4. 6m - 9m = -3m
  5. Plug -3m in: -3m = 21
  6. Divide each side by -3 to cancel out the -3 next to x. It should now look like this: m = -7

I hope this helps!